Diagnosis of respiratory epithelial clearance abnormality in patients suffering from chemo-resistant pulmonary tuberculosis with comorbidity of bronchial mucosa - O. M. Raznatovska; V. M. Khlystun (Zaporozhye State Medical University, 2018)
Abstract Respiratory epithelial clearance timely and early disorder diagnosis in patients suffering from chemo-resistant pulmonary tuberculosis (CRPTB) concomitant pathology of the bronchial mucosa is an actual problem of modern phthisiology, the solution of which will allow the timely application of rational correction, which will increase the effectiveness of this category treatment among patients. Objective is to investigate the nature and features of respiratory epithelial clearance disorders among patients suffering from CRPTB with comorbidity of the bronchi mucous membrane by using the developed method of these disorders diagnosis. Materials and methods. The respiratory epithelial clearance state diagnosis was carried out among 133 patients with CRPTB at the beginning of the intensive phase of antimycobacterial therapy during fibrobronchoscopy, provided there is a concomitant specific pathology of the mucous membrane (including its combination with non-specific endobronchitis). Average age of patients was 36.5 ± 1.1 years old. There were 89 (66.9 %) men and 44 (33.1 %) women. The tracheobronchial tree diagnostic fibrobronchoscopy with further study of the respiratory epithelial clearance condition among patients suffering from CRPTB was carried out by V. M. Khlystun at Phthisiology and Pulmonology Department of Zaporizhzhia State Medical University in CI "Zaporizhzhia Regional Antituberculous Clinical Dispensary". Criteria of patients including into the research: existence of resistance of tuberculosis mycobacteria to anti-mycobacterial drugs in patients with new and repeated cases of tuberculosis, existence of pathology of the mucosa of bronchi confirmed during fiberoptic bronchoscopy. Serious associated diseases (HIV infection/AIDS, diabetes mellitus, etc.) were criteria of exception. The condition of bronchial mucosa was studied under narcotic anaesthesia by fiberoptic bronchoscopes of Olympus (Japan). Pathology of a bronchial tree was described according to classification by M. V. Shesterina, A. N. Kalyuk (1975). Results of the research are processed by modern methods of the analysis using the personal computer with the statistical package Statistica® for Windows 6.0 license program (StatSoft Inc., No. AXXR712 D833214FAN5). Results. There were respiratory epithelial clearance disturbances in 94.7 %, which predominate with the 1st and 2nd stages of mucociliary inefficiency (51.1 % and 37.6 %). There was mucociliary inefficiency dependence on the bronchi mucous membrane pathology nature: the incidence of respiratory epithelial clearance in patients with concomitant bronchial tuberculosis in combination with the nonspecific purulent endobronchitis is 2.4 times higher than in those with concomitant bronchial tuberculosis only (70.7 % vs 29.3 %). The association of nonspecific purulent endobronchitis with concomitant bronchial tuberculosis leads to an increase in the mucociliary inefficiency degree of severity, due to its diffuse localization, where it is diagnosed more often than in the limited one, thus, mucociliary inefficiency of the 2nd stage of severity (64.9 % vs 24.6 %, is 2.6 times more (64.9 % vs 24.6 %) and 4.6 times more in the 3rd stage (16.2 % vs 3.5 %). Conclusions. The proposed method for the diagnosis of mucociliary inefficiency disorders among patients suffering from CRPTB with bronchial mucosa concomitant pathology allows to diagnose mucociliary inefficiency and mucociliary inefficiency dependence on the bronchi mucous membrane pathology nature.